2012
DOI: 10.1152/ajpendo.00619.2011
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming of neonatal pancreatic β-cells by a maternal low-protein diet in rats involves a switch from proliferation to differentiation

Abstract: Maternal low-protein diets (LP) impair pancreatic β-cell development, resulting in later-life failure and susceptibility to type 2 diabetes (T2D). We hypothesized that intrauterine and/or postnatal developmental programming seen in this situation involve altered β-cell structure and relative time course of expression of genes critical to β-cell differentiation and growth. Pregnant Wistar rats were fed either control (C) 20% or restricted (R) 6% protein diets during pregnancy (1st letter) and/or lactation (2nd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 47 publications
2
36
2
Order By: Relevance
“…1a, b) in accordance with data from previous studies [12,13]. The microarray analysis of the transcriptome from rat pup pancreases revealed several genes as being differentially expressed.…”
Section: Maternal Lp Dietsupporting
confidence: 89%
See 3 more Smart Citations
“…1a, b) in accordance with data from previous studies [12,13]. The microarray analysis of the transcriptome from rat pup pancreases revealed several genes as being differentially expressed.…”
Section: Maternal Lp Dietsupporting
confidence: 89%
“…Despite the GAS6-induced reduction in Mafa observed in this study, the Mafb mRNA content in GAS6-treated neonatal rat islets was unchanged. It was recently reported that a maternal LP diet increases the levels of factors in offspring associated with mature beta cells (among others Slc2a2; a target of MAFA) [13]. Rodriguez-Trejo et al [13] suggested that the maternal LP diet changed the uterine environment to favour maturation of beta cells at the expense of proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HNF1A may also be involved in metabolic programming of the fetus (Rodriguez-Trejo et al 2012). An interesting finding from this study is the change with parturition in various proteins involved in triglyceride transport and metabolism.…”
Section: Hnf1a Is a Key Mediator Of Human Parturitionmentioning
confidence: 99%